Adaptive system of education in the primary school - E R Moskalets (Peoples' Friendship University of Russia (RUDN University), 2010)
In this article we considered characteristics of using adaptive system of education on the primary stage of education, disclosed the goals, which typical for the primary school, compared traditional and adaptive system of education.